Multiplex PCR for the detection of 10 viruses causing encephalitis/encephalopathy and its application to clinical samples collected from Japanese children with suspected viral encephalitis/encephalopathy - Pham N. (2017)
Background: Acute encephalitis is a serious neurological condition having a high mortality rate and affecting both children and adults. This study aimed to develop a multiplex PCR method for the simultaneous screening of clinical samples for the presence of the 10 viruses presently considered as the major viral causes of acute encephalitis/encephalopathy in Asia. Methods: Using previously published primers that have been widely used to screen for herpes virus-6, influenza A virus, human parechovirus, herpes simplex viruses 1 and 2, Japanese encephalitis virus, group A rotavirus, enterovirus, adenovirus, and dengue virus in clinical samples, a single-tube multiplex PCR assay was developed and was tested for its sensitivity and specificity. The method was then applied to screen 57 clinical samples, consisting of 13 fecal samples, 5 throat swabs, 3 post-nasal swabs, 18 serum samples, and 18 cerebrospinal fluid (CSF) samples, collected from 18 hospitalized Japanese children with suspected viral encephalitis/encephalopathy for the target viruses, and the results were compared with those of a monoplex PCR method. Results: Positive viral controls of the 10 viruses were correctly typed using this multiplex PCR method. The multiplex PCR method showed high specificity with no unspecific amplification to non-target viruses. The results of applying this PCR method for screening clinical samples showed that 6 fecal samples, 2 serum samples, and 1 CSF sample collected from 7 patients were positive for a virus, specifically group A rotavirus (4 patients, 22.2%), enterovirus (2 patients, 11.1%), or adenovirus (1 patient, 5.6%). In comparison with monoplex PCR, for group A rotavirus, enterovirus, and adenovirus, the sensitivity of this multiplex PCR method decreased for serum, cerebrospinal fluid, and throat swab samples. Conclusions: This newly developed multiplex PCR method is a simple, rapid diagnostic tool and can be used to screen clinical samples for viruses causing acute encephalitis/encephalopathy in children in Asian countries.